Affect, Albert Ellis, and Rational-Emotive Therapy - Morris, G. Barry (Canadian Journal of Counselling and Psychotherapy, 2011)
The theme is advanced that affect is an integral component of the Rational-Emotive Therapy model. The affective aspect of the model is reviewed in terms of theoretical constructs and therapeutic techniques. Several references to author-observed interactions of Albert Ellis are made and the life-style of Albert Ellis is described to permit inferences regarding the role of affect.